Increasing the Students’ Writing Skill through Blended Learning Model at The Tenth Graders of MAN 2 Lamongan - Daniar Sofeny; Alvin Khusnia (Edulitics (Education, Literature, and Linguistics) Journal, 2020)
The research was conducted to find out the implementation of blended learning in writing recount text, the result of students’ work and the students’ response toward blended learning model. This research used descriptive qualitative as the research design. The subjects are 37 students of X-Bahasa class and an English teacher. The researcher was observed the teaching and learning process using blended learning. Then, the researcher analyzed the result of students work in recount text using rubric and conducted interview with six students. The result showed that the implementation of blended was in accordance with blended learning process, namely learning design, content production and content delivery. The analysis of students’ work showed that students had developed in writing recount text. Students wrote a recount text that related with the content and structure of recount text but students still made mistakes on grammar aspects. Students’ response showed that the easy access of information and implementation of blended learning had helped them comprehend the lesson. However, the problems of using blended learning were internet network and the amount of information available on the internet.